Electron-density distribution and disordered crystal structure of 12H-SiAlON, SiAl5O2N5. Issue 4 (10th June 2014) - Banno, Hiroki; Hanai, Takaaki; Asaka, Toru; Kimoto, Koji; Nakano, Hiromi; Fukuda, Koichiro
<x content-type="archive" xml:space="preserve">Abstract</x> The crystal structure of SiAl5O2N5 was characterized by laboratory X-ray powder diffraction (CuKα1). The title compound is hexagonal with space group P63/mmc (Z = 2). The unit-cell dimensions are a = 0.303153(3) nm, c = 3.28153(3) nm, and V = 0.261178(5) nm3. The initial structural model was successfully derived by the direct methods and further refined by the Rietveld method. The final structural model showed the positional disordering of two of the four (Si, Al) sites. The maximum-entropy method-based pattern fitting (MPF) method was used to confirm the validity of the split-atom model, in which conventional structure bias caused by assuming intensity partitioning was minimized. The reliability indices calculated from the MPF were Rwp = 5.00%, S (=Rwp/Re) = 1.25, Rp = 3.76%, RB = 1.26%, and RF = 0.90%. The disordered crystal structure was successfully described by overlapping four types of domains with ordered atom arrangements. The distribution of atomic positions in each of the domains can be achieved in the space group P63mc. Two of the four types of domains are related by a pseudo-symmetry inversion, and the two remaining domains also have each other the inversion pseudo-symmetry.